Peran Model Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Terhadap Keterampilan Menulis - Alizunna, Defirra; Mukarromah, Aenullael (Jurnal el-Huda, 2025)
This study aims to examine in depth the role of the Cooperative Integrated Reading and Composition (CIRC) learning model on writing skills through a literature review approach. The low writing skills of elementary school students remain a complex issue, characterized by weak ideas, paragraph organization, vocabulary use, and writing mechanics. Previous studies have shown that the CIRC model integrates reading and writing activities in a collaborative setting, positively impacting literacy skills. This article analyzes empirical findings from various relevant studies on the implementation of CIRC in language learning, particularly writing skills. The results indicate that CIRC implementation can improve the quality of students' writing in terms of content, organization, and language use. These findings confirm that CIRC is a suitable alternative innovative learning model to support elementary school literacy programs.